Identification and Mapping of Landslide-Prone Areas in the Meninting Watershed Area, West of Lombok - Arben Virgota; Baiq Farista (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The Meninting Watershed (DAS) covers several areas in West Lombok Regency, Mataram City and a small part of North Lombok Regency. Characteristics of a very steep topographic watershed (DAS) triggers landslides. Landslide is the process of moving rock and soil masses from high places to lower places under the influence of gravity. Landslides can cause great physical damage and economic losses, therefore research on landslides is urgently needed. This study aims to identify and map landslide-prone areas in the Meninting Watershed. This study uses a geographic information system (GIS) approach, namely the overlay method (overlapping) and scoring (weighting). Some of the parameters used to assess the level of landslide vulnerability are slope, soil type, land cover rainfall and geological aspects. The level of landslide vulnerability is divided into 3 namely low, medium and high. The results showed that an area of 2,411.42 ha or around +20% of the area of the Meninting Watershed is a high-level landslide-prone area. The area that is included in the medium-level landslide-prone category is around 7,010.03 ha or + 57% of the Meninting Watershed area. Bukittinggi Village and Kekait Village, Gunungsari District, have the greatest potential for medium and high scale landslides.